Green Lecture dan Penanaman Mangrove Di Kawasan Ekowisata Lantebung - Harry Yulianto; Iryani Iryani (Lembaga Pengembangan Kinerja Dosen, 2024)
Coastal areas are transition areas between land and sea ecosystems that have various potential natural resources, but the increasing rate of abrasion can be a threat to ecosystem life in coastal areas. The problem that often occurs in ecotourism development is excessive use of natural resources for tourism activities without considering the carrying capacity of the area so damaged mangrove ecosystems are often found as a result of excessive tourism activities and without good management. The service activities aim to: 1) provide college student with an understanding of the importance of preserving the natural environment, 2) plant mangrove seedlings in the Lantebung ecotourism area, and 3) introduce college student to the Lantebung ecotourism destination. Methods for implementing activities are socialization and Participatory Rural Appraisal. The analysis technique used is descriptive statistics. The results of the evaluation of the implementation of activities indicate the following: 1) increased college student knowledge in preserving nature, 2) increased college student knowledge about the impacts of coastal erosion, 3) increased college student understanding of the Tridharma of higher education, 4) increased college student knowledge about the impacts of extreme weather, 5) increased college student knowledge about the impacts of extreme weather, 5) increasing college student knowledge about Lantebung ecotourism destinations, as well as 6) carrying out activities to plant mangrove seedlings in the Lantebung ecotourism area.